Biocides in Soils of Urban Stormwater Infiltration Systems—Indications of Inputs from Point and Non-point Sources - Linke, Felicia; Edun, Omoyemi; Junginger, Tobias; Payraudeau, Sylvain; Preusser, Frank; Imfeld, Gwenaël; Lange, Jens (Water, air, and soil pollution, 2023)
Urban stormwater contains various micropollutants, such as biocides, which are washed off from facades during wind-driven rain events. Biocides can reach the groundwater via stormwater infiltration systems (SIS), although the soil layer acts as a reactive barrier preventing the leaching of biocides but producing transformation products (TPs). Little is known about the occurrence and concentration of biocides in SIS soils, their distribution and temporal behavior. Here, we present a first systematic screening of three commonly used biocides (diuron, octylisothiazolinone (OIT), terbutryn) and four TPs of terbutryn in 46 French and German SIS. Overall, biocide occurrence in SIS topsoils was ubiquitous but low, while point source inputs to specific SIS were high but rare. Low concentrations (< 2ng g -1 ) of terbutryn were detected in 78% of the SIS. Maximum concentrations occurred in recently constructed SIS, suggesting that this is due to higher biocide loads entering the SIS. The frequent detection of terbutryn supports the idea that it is a non-point source marker, as it is relatively stable in soil (t 1/2 > 90 days) and widely used in renders and paints. In contrast, high concentrations of diuron (168 ng g -1 ) and OIT (58 ng g -1 ) were observed in only one sample, suggesting an urban point source contamination, possibly from a freshly repainted facade. The distinction between source types provides a basis for targeted measures to prevent biocide entry to groundwater. Altogether, this study opens the door to a more systematic consideration of micropollutant dissipation and ecotoxicological effects in SIS design and monitoring.